63例儿童流行性感冒合并塑型性支气管炎的临床特征分析 (Zhongguo Dang Dai Er Ke Za Zhi, 2020)
OBJECTIVE: To study the clinical features of children with influenza and plastic bronchitis (PB). METHODS: A retrospective analysis was performed on the medical data of 63 children with influenza and PB, including clinical manifestations, laboratory examination results, imaging findings, treatment, and outcome. RESULTS: Among the 63 children, there were 52 boys (83%) and 11 girls (17%), and 42 children had influenza A and 21 had influenza B. Among these children, 38 (60%) aged 3-6 years, and 15 (24%) had underlying diseases. The main clinical manifestations were high fever (90%), cough (95%), and shortness of breath (73%). Twenty-four children (38%) were found to have atelectasis by imaging examination. Auscultation showed that 16 children (25%) had no rales in the lungs. Of all children, 41 were admitted to the intensive care unit, and 32 required mechanical ventilation. All children underwent fiberoptic bronchoscopy and alveolar lavage. Among the 63 children, 60 recovered and 3 died. CONCLUSIONS: Influenza with PB is often observed in boys and preschool children. For influenza children with shortness of breath, even if there is no atelectasis on chest X-ray or no rales are found by auscultation, the possibility of PB still needs to be considered.